Determination of Volumetric Mass Transfer Coefficient in Fixed Bed Adsorption - A. Al-Hemiri, Adil; Y. Al-Kaisy, Farah (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
This work was conducted to determine the volumetric mass transfer coefficient (Ky.a) infixed bed adsorption using hexane-benzene mixture by adsorption onto a fixed bed of white silica gel. Benzene concentration was measured by gas chromatography. The effect of feed flow rate and initial concentration of benzene in hexane-benzene mixture on the volumetric mass transfer coefficient and on the adsorption capacity of silica gel was investigated. In general, the volumetric mass transfer coefficient increases with increasing hexane flow rate, and with increasing initial concentration of benzene in the mixture. The ultimate value of (Ky.a) was at 53 ml/min of hexane flow rate with benzene initial concentration of (6.53 wt. %), and it was (99.4 kg/m3.s). The adsorptive capacity of silica gel increases with decreasing hexane flow rate, as with increasing initial concentration of benzene in the mixture. The best adsorptive capacity of the imported silica gel (100 g of imported silica gel yielded 120 ml of benzene-free effluent) was achieved with the grade (1.18-5 mm) in size at a hexane flow rate 15 ml/min.